2009
DOI: 10.1007/s00464-009-0330-9
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the donor pool: use of right kidneys and kidneys with multiple arteries for live donor transplantation

Abstract: The presence of multiple arteries or the need to procure the right kidney does not affect the operative outcome of laparoscopic donor nephrectomy. Warm ischemia time may be greater for these groups, but this does not result in delayed allograft function. The laparoscopic approach should be the standard of care even when expansion of the donor pool includes organs with multiple arteries and procurement of the right kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…No significant difference in estimated blood loss, transfusions, operative time or length of hospital stay was noted between multiple and single laparoscopic donor nephrectomies. 4 Benedetti et al reported the same results among 163 patients with MRA versus 835 with single renal arteries. 5 Available studies support that donor morbidity and recipient intraoperative, early and late postoperative outcomes do not differ between donors with multiple renal arteries and those with a single renal artery.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…No significant difference in estimated blood loss, transfusions, operative time or length of hospital stay was noted between multiple and single laparoscopic donor nephrectomies. 4 Benedetti et al reported the same results among 163 patients with MRA versus 835 with single renal arteries. 5 Available studies support that donor morbidity and recipient intraoperative, early and late postoperative outcomes do not differ between donors with multiple renal arteries and those with a single renal artery.…”
supporting
confidence: 65%
“…Although symmetrical peripheral oedema is well documented with the use of sirolimus, there are limited reports of single limb lymphoedema. [1][2][3][4] A 59 year old woman with a stable renal allograft for 17 years, presented with extensive and debilitating unilateral swelling of the entire left arm following a suspected insect bite 2 weeks before presentation. She had a functioning radiocephalic fistula in the affected arm.…”
Section: Matthew J Damasiewicz and Francesco L Ierino Department Of mentioning
confidence: 99%
“…We believe that technical concerns, particularly related to the short renal vein, in conjunction with increasing familiarity with the laparoscopic technique leading to a comfort level in the use of left-sided kidneys with multiple renal arteries, explain the continued preference for left-sided kidney use (2,12,21). Interestingly, the declining proportion of right-sided kidneys has taken place despite a series of studies reporting similar outcomes between right and left kidneys recovered using LDN.…”
Section: Discussionmentioning
confidence: 87%
“…Liu et al reported similar surgical outcomes in 19 left-sided HALDNs and 6 right-sided HALDNs [9]. Keller et al reported that 36 right-sided procedures out of 230 LDNs showed similar results in EBL, amount of blood transfusion, operative time, LOS, and delayed graft function compared with left-sided HALDN [20]. There have been more reports about the excellent surgical outcomes of right laparoscopic donor nephrectomy compared with left-sided operations [21-23].…”
Section: Discussionmentioning
confidence: 99%